The effect of crude extract of centella asiatica on voltage-gated sodium hannel (VGSC) media ted motility on mda-mb-231 breast cancer cell lines - Rusli, Noradliyanti (2013)
Voltage-gated sodium channel (VGSC) has been found to plays a role in metastasis as it help in the cancer cells adhesion, motility, secretion as well as invasion. Breast cancer also shows these properties with neonatal Nav 1.5 to be highly expressed and it is one of the isoform of the VGSC. This suggests VGSC, specifically neonatal Navl.S to be used as a target for a new drug development for breast cancer treatment and for anti-metastasis drug. Cente/la asiatica is one of plant or herb that being used in traditional and alternative medicine to help cure certain disease or disorder including epilepsy and cognitive disorder as well as cancer. Thus, in this project, the effect of the Centella asiatica on the voltagegated sodium channel activities and motility of the MDA-MB-231 breast cancer cell lines have been studied. The mechanism on how the plant extract shows an effect to metastasis also being explored by doing a molecular study on the expression of the neonatal Navl.S. Four different assays are being used in the determination of the effect which includes MIT assay, Trypan Blue assay, motility assay and molecular study. There is no effect of the plant extract on the proliferation and viability and toxicity assay but there is an effect on the motility of the cells. As there is no effect of the plant extract on the cells proliferation and viability, the effect that can be seen on the motility is genuinely produce by the plant extract on cell's motility not because of it also affect proliferation and cells viability. From a molecular study, it has been shown that there is a decrease in the neonatal Nav l.S expression and this support the fact that the plant extract reduce the migration rate by decreasing or down-regulating the neonatal Navl.S expression. In conclusion, this plant crude extract has a great potential to be used in the anti-metastasis drug development specifically on breast cancer which expressed neonatal Navl.S.